Pengaruh dana pihak ketiga, kecukupan modal dan penyaluran kredit terhadap profitabilitas bank - Sudarmin Parenrengi; Tyahya Whisnu Hendratni (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
This study aims to provide empirical evidence about the effect of DPK (Third Party Funds), CAR (Capital Adequacy Ratio), LDR (Loan to Deposit Ratio), and BOPO (Operating Expenses to Operating Income) on the profitability (ROA) of state banks. The multiple linear regression with classic assumption test was used to hypothesis testing. The results showed that DPK, LDR, and BOPO had a positive and significant effect on ROA, while CAR has no significantly effect. Among all the independent variables studied, DPK is the dominant variable affecting ROA, and, ROA can explained by the variables studied at 81.4% while the remainder was explained by other factors not included in the study.